Phosphine and phosphine oxide groups in metal–organic frameworks detected by P K-edge XAS. Issue 5 (19th December 2014) - Morel, F. L.; Pin, S.; Huthwelker, T.; Ranocchiari, M.; van Bokhoven, J. A.
Abstract : The synthesis of phosphine-functionalized metal–organic frameworks frequently leads to the formation of different phosphorus environment inside the framework. We used P K-edge X-ray absorption spectroscopy to quantify phosphine and phosphine oxide groups inside two frameworks with MIL-101 topology. Abstract : Phosphine metal–organic frameworks (P-MOFs) are crystalline porous coordination polymers that contain phosphorus functional groups within their pores. We present the use of X-ray absorption spectroscopy (XAS) at the P K-edge to determine the phosphine to phosphine oxide ratio in two P-MOFs with MIL-101 topology. The phosphorus oxidation state is of particular interest as it strongly influences the coordination affinity of these materials for transition metals. This method can determine the oxidation state of phosphorus even when the material contains paramagnetic nuclei, differently from NMR spectroscopy. We observed that phosphine in LSK-15 accounts for 72 ± 4% of the total phosphorus groups and that LSK-12 contains only phosphine oxide.